Information Retrieval System for Malaysian Association for the Blind (MAB) - MAT AYOB, NUR AMYLIA WAHIDA; AMAN, MUHAMMAD SHUKRI; AHMAD JAMEL, MUHAMAD SYAHRUL SYAZWAN; SOOSAY NATHAN, SHELENA (Multidisciplinary Applied Research and Innovation, 2024)
The Malaysian Association of the Blind (MAB) is a voluntary organization in Malaysia that provides services to the visually impaired. Achieving substantive equality in all aspects of life is one of the main principles held by MAB in fighting for the rights of the visually impaired community. At the same time, the MAB are also providing research information regarding the visually impaired studies conducted so that people in search of such information and research details will be beneficial. There is a need for an information retrieval system which can keep the research information that can be retrieved by the user within or outside MAB. This system is targeted for researchers within MAB or common user in search of references and literature related to the visually impaired. This system uses the waterfall method which acts as a guide throughout the development of this project, the phases are such as analysis, design, implementation, testing, deployment and maintenance. phpMyAdmin as some of the related software used in the development process of the system alongside HTML and CSS. The developed system was then tested with the MAB staff and user where 30 users participated in the process. The result of the testing shows that 85% of the users are satisfied and feel the system is easy for them to use and find information. Besides that, the system also allows the admin to always update the information in the system easily to be reached out to the users. As conclusion, the system is capable of being used for the MAB user and public that ease the process of retrieving information.